Novel Chitosan Coated Magnetic Nanocarriers for the Targeted Diclofenac Delivery - Agotegaray, Mariela Alejandra (2014)
New magnetic devices consisting of magnetite functionalized with oleic acid and Chitosan have been synthesized and employed to the loading of Diclofenac as potential tool for treatment of targeted inflammatory diseases. Magnetic loaded and un-loaded nanoparticles have been thoroughly characterized by infrared spectroscopy, ransmission electron microscopy, determination of hydrodynamic diameter by Dynamic light scattering and zeta potential measurements at different pH conditions. A study of the release of Diclofenac has been performed in vitro and available mathematical models have been used to determine the release kinetic. Both properties and release data reveal that this nanomagnetic platform would be suitable for in vivo assays.